The VEGF-induced transcriptional response comprises gene clusters at the crossroad of angiogenesis and inflammation - Schweighofer, Bernhard; Testori, Julia; Sturtzel, Caterina; Sattler, Susanne; Mayer, Herbert; Wagner, Oswald; Bilban, Martin; Hofer, Erhard (Thrombosis and Haemostasis, 2009)
VEGF-A is the major trigger of vasculogenesis and physiologic angiogenesis. We have investigated to which extent the gene repertoire induced by VEGF-A in endothelial cells is distinct from that of other growth factors and inflammatory cytokines. Genes upregulated in human umbilical vein endothelial cells treated with VEGF, EGF or IL-1 were compared by microarray analysis and clusters characteristic for individual or combinations of inducers were defined. VEGF-A upregulated in comparison to EGF a five-fold larger gene repertoire, which surprisingly overlapped to 60% with the inflammatory repertoire of IL-1. As shown by real-time RT-PCR for selected genes, VEGFinduction was mostly mediated by VEGF receptor-2 and the capacity of VEGF-A to induce genes in common with IL-1 largely depended on activation of the calcineurin/NFAT pathway, since cyclosporin A inhibited this induction. Another angiogenic growth factor, bFGF, did not share a comparable induction of inflammatory genes, but partially induced a small group of genes in common with VEGF-A, which were not regulated by EGF. Thus, the data display that VEGF-A induces a distinct gene repertoire, which, contrasting with other growth factors such as EGF or bFGF, includes an inherent inflammatory component possibly contributing to the cross-regulation of angiogenesis and inflammation as further indicated by the VEGF-mediated induction of leukocyte adhesion. Furthermore, a small group of genes selectively induced by VEGF-A with potential importance for angiogenesis is defined.
Keywords: VEGF-A; endothelial cells; angiogenesis; inflammation; gene repertoire